The regulatory effect of herd structure on pig production under the environmental regulation. - Gangyi Wang; Yuzhuo Shen; Chunlei Li; Qiuping Zhu; Aidyn ZhanBota (PLoS ONE, 2022)
Integrating pig production stability and pollution control is a matter of social livelihood and green development. This paper estimates the policy effectiveness of environmental regulation based on the big data of Chinese government websites and combines the pig production data of various provinces in China from 2008 to 2018 to construct a mediating effect model, empirically analyzing the relationship between environmental regulations, herd structure, and pig production. Research shows: (1) Improving environmental regulations in the short term will increase the slaughter of pigs, but in the long run it will decrease first and then increase; (2) At this stage, environmental regulations can increase the slaughter of pigs by changing the herd structure; (3) Reasonable adjustment of the herd structure can effectively increase the slaughter of pigs; (4) The herd structure can be used as a supplementary monitoring indicator to stabilize the supply of pigs. Combine it with the change rate of sow stock to provide early warning of fluctuations in pig production, and the early warning herd structure values are 0.0980 and 0.1135. There are two key initiatives to achieve supply and price stability in the pig industry that taking into account environmental protection: first, an industrial regulation instrument based on the herd structure needs to be established; second, an early warning system for pig production fluctuations should be established with reference to the early warning system for pork price fluctuations.